DAMPAK PEMUKIMAN DAN KEGIATAN DI TEPI SUNGAI TERHADAP KUALITAS AIR SUNGAI BARU BARAT - Ariane Pratiwi; Melati Ferianita Fachrul; Diana Irvindiaty Hendrawan (ITB Journal Publisher, LPPM ITB, 2020)
Abstract. Baru Barat River is a man made river for flood and irrigation control. This study aims to determine the effect of activities on the bank on Baru Barat River on the water quality. Identification of activities is carried out along the bank of river. Water quality parameters are compared with the Governor of Jakarta no. 582 year 2005. The status of water quality is determined using the Pollution Inde (PI). The activities around the Baru Barat River are settlements, officem workshop, schools, deales, food stall, laundry, shops, beauty salons, guesthouses and gas station. BOD concentration range from 8.4-43.7 mg/L with a quality standard of 10 mg/L and COD range from 16-99.2 mg/L with a quality standard of 20 mg/L. Concentration of BOD and COD that exceed of quality standard at almost all sampling ponts. The level of pollutionj in the Baru Barat River is moderate polluted. The main problem at Baru Barat River are the presence of several illegal waste point left from activities that eventually enter the river and the absence of waste water treatment. The concept of community based must be implemented to waste management and communal wastewater treatment that are easy, inexpensive and integrated with the landscape. Keywords: Baru Barat River, river bank, water pollution index, river quality, domestic waste water